Functional outcome of autologous anorectal transplantation in an experimental model. Issue 5 (18th February 2015) - Seid, V. E.; Galvão, F. H. F.; Vaidya, A.; Waisberg, D. R.; Cruz, R. J.; Chaib, E.; Nahas, S. C.; Araujo, S. E. A.; D'Albuquerque, L. A. C.; Araki, J.
<x xml:space="preserve">Abstract</x> Background Although anorectal transplantation is a challenging procedure, it is a promising option for patients who have completely lost anorectal function or in whom it failed to develop, as in congenital malformations. The paucity of animal models with which to test functional outcomes was addressed in this study of anorectal manometry in rats. Methods Wistar rats were assigned randomly to four groups: orthotopic anorectal transplantation, heterotopic transplantation, sham operation, or normal control. Bodyweight and anal pressure were measured immediately before and after operation, and on postoperative days 7 and 14. ANOVA and Tukey's test were used to compare results for bodyweight, anal manometry and length of procedure. Results Immediately after the procedure, mean(s.d.) anal pressure in the orthotopic group (n = 13) dropped from 31·4(13·1) to 1·6(13·1) cmH2O (P < 0·001 versus both sham operation (n = 13) and normal control (n = 15)), with partial recovery on postoperative day 7 (14·9(13·9) cmH2O) (P = 0·009 versus normal control) and complete recovery on day 14 (23·7(12·2) cmH2O). Heterotopic rats (n = 14) demonstrated partial functional recovery: mean(s.d.) anal pressure was 26·9(10·9) cmH2O before operation and 8·6(6·8) cmH2O on postoperative day 14 (P < 0·001 versus both sham and normal control). Conclusion Orthotopic anorectal transplantation may result in better functional outcomes than heterotopic procedures.<boxed-text content-type="box" id="bjs9762-blkfxd-0001" position="anchor" orientation="portrait"> Surgical relevance Patients with a permanent colostomy have limited continence. Treatment options are available, but anorectal transplantation may offer hope. Some experimental studies have been conducted, but available data are currently insufficient to translate into a clinical option. This paper details functional outcomes in a rat model of anorectal autotransplantation. It represents a step in the translational research that may lead to restoration of anorectal function in patients who have lost or have failed to develop it. </boxed-text>